SURVEI MANAJEMAN ORGANISASI PADA FITNESS CENTER MARS GYM KOTA MAKASSAR - Sensy Karnia; Ainul Hidayah (Journal of Innovation Research and Knowledge, 2024)
In this research design, research subjects were selected using purposive sampling based on certain characteristics to become a research group so that the research subjects were homogeneous. The research subjects in this study were 2 managers, 8 personal trainers, 15 members, a total of 25. The variables in this research were planning, organizing, implementing and evaluating, while data analysis used SPSS 21 using descriptive tests, normality tests and hypothesis tests. Based on the results of the analysis, the results of data processing, it can be seen that the analysis of organizational management at MASR Gym in the city of Makassar obtained percentage results on the Planning variable which was supported by 21 respondents in the moderate category, while 4 respondents were in the very poor category, Organizing was supported by 20 respondents. included in the moderate category, while 5 respondents were in the very poor category, the implementation was supported with 24 respondents being in the moderate category, while 1 respondent was in the very poor category, the evaluation was supported with 24 respondents being in the moderate category, while 1 respondent falls into the very low category